Characterization of the Signaling Modalities of Prostaglandin E2 Receptors EP2 and EP4 Reveals Crosstalk and a Role for Microtubules - Vleeshouwers, Ward; van den Dries, Koen; de Keijzer, Sandra; Joosten, Ben; Lidke, Diane S.; Cambi, Alessandra (Frontiers in Immunology, 2021)
Prostaglandin E2 (PGE2) is a lipid mediator that modulates the function of myeloid immune cells such as macrophages and dendritic cells (DCs) through the activation of the G protein-coupled receptors EP2 and EP4. While both EP2 and EP4 signalling leads to an elevation of intracellular cyclic adenosine monophosphate (cAMP) levels through the stimulating Gαs protein, EP4 also couples to the inhibitory Gαi protein to decrease the production of cAMP. The receptor-specific contributions to downstream immune modulatory functions are still poorly defined. Here, we employed quantitative imaging methods to characterise the early EP2 and EP4 signalling events in myeloid cells and their contribution to the dissolution of adhesion structures called podosomes, which is a first and essential step in DC maturation. We first show that podosome loss in DCs is primarily mediated by EP4. Next, we demonstrate that EP2 and EP4 signalling leads to distinct cAMP production profiles, with EP4 inducing a transient cAMP response and EP2 inducing a sustained cAMP response only at high PGE2 levels. We further find that simultaneous EP2 and EP4 stimulation attenuates cAMP production, suggesting a reciprocal control of EP2 and EP4 signalling. Finally, we demonstrate that efficient signalling of both EP2 and EP4 relies on an intact microtubule network. Together, these results enhance our understanding of early EP2 and EP4 signalling in myeloid cells. Considering that modulation of PGE2 signalling is regarded as an important therapeutic possibility in anti-tumour immunotherapy, our findings may facilitate the development of efficient and specific immune modulators of PGE2 receptors.